Effectiveness of DPP-4 vs SGLT2 Inhibitors on Cardiovascular Parameters in Type 2 Diabetes Animal Models: A Literature Review - Juanti, Putri; Indrisari, Maulita; Pascayantri, Asniar (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2025)
Introduction: As a chronic metabolic disease, type 2 diabetes mellitus (T2DM) is strongly correlated with a heightened risk of cardiovascular disease through mechanisms involving endothelial dysfunction, chronic inflammation, oxidative stress, and myocardial fibrosis. The management of cardiovascular complications in T2DM has encouraged research on antidiabetic agents with cardioprotective effects. Two drug classes that have been extensively studied, namely dipeptidyl peptidase-4 inhibitors (DPP-4i) and sodium-glucose cotransporter 2 inhibitors (SGLT2i), demonstrate distinct mechanisms and potential for cardiovascular protection. Aims: Compare the effectiveness of DPP-4i and SGLT2i on cardiovascular parameters in T2DM animal models. Method: A rigorous systematic review was performed across Google Scholar and PubMed databases, adhering to the predefined inclusion parameters of preclinical studies in T2DM animal models evaluating the effects of DPP-4i and/or SGLT2i on cardiac function, blood pressure, myocardial fibrosis, oxidative stress, and inflammatory biomarkers. Result: The findings indicate that SGLT2i are more effective in improving systolic and diastolic functions, reducing myocardial fibrosis, and attenuating oxidative stress, whereas DPP-4i show superior impact in modulating inflammation, enhancing diastolic function, and providing protection against ischemia–reperfusion injury. Conclusion: DPP-4i and SGLT2i exert complementary cardioprotective effects through different mechanisms. These findings suggest that combination therapy may be an optimal strategy to prevent cardiovascular complications in T2DM.